Dissolution properties, solid-state transformation and polymorphic crystallization: progesterone case study - Araya-Sibaja, Andrea Mariela (2014)
Fil: Araya-Sibaja, Andrea Mariela. Universidade Federal de Santa Catarina. Programa de Pós-Graduação em Farmácia; Brasil.